Heroic past versus Un-heroic Present: The Politics of Memory and its Discontents - Potkonjak, Sanja (2008)
The aim of this paper is to cross-reference the discourse on antifascism and Europeanism. By presenting three Croatian art projects which are dealing with postsocialism, the paper focuses on institutional and everyday strategies of identity creation.